Clinical and haematological Findings in Sudanese patients With sickle cell disease Attending the hospitals in Elobeid, Kordofan - Mohammed, Hala Ibrahim; Abdalla Agabeldoor, Ahmed; Khalid, Khalid Eltahir; Ali, Khalid Eltom (Gezira Journal of Health Sciences, 2006)
Objectives: This study aimed at assessing the clinical features and haematological parameters in sickler Sudanese patients attending El Obeid Hospitals in North Kordofan, Sudan. Materials and Methods: Eighty five patients with homozygous sickle cell (SS) disease, (both sexes) were included in this study. Their age ranged between 6 months to 42 years. Forty persons were used as control. Clinical manifestations were recorded at examination. Freshly obtained blood samples from patients and control were used to estimate haematological parameters which included: haemoglobin concentration (Hb), packed cell volume (PCV), red blood cell count (RBC), white blood cell count (WBC), mean corpuscular haemoglobin (MCH), mean corpuscular volume (MCV), and erythrocyte sedimentation rate (E.S.R).                Results: The clinical investigations revealed that all patients presented with painful crisis, 96.5% had chronic anemia, 84.7% had recurrent malaria and 81.2% had different infections (76% was chest infection). 32.9% of the sickle cell disease (SCD) patients had no blood transfusion, while the rest had blood transfused once to five times. Haematological measurement indicate that all SCD patients in this study were reported anaemic, and their Hb, PCV and RBC count were significantly lower (P<0.001) compared with the control group, while WBC count and MCV were significantly higher (P<0.001, P<0.01). In this study the prevalence of SCD in Misseria tribe (24.7%) was highest compared to other tribes. Conclusion: This study affirmed the problem of sickle cell disease in Kordofan state, which should draw attention toward the need of further studies.